Bebelier – Atelier para niños - Chavez Arancibia, Susana (2023)
The current investigation evaluates the feasibility and commercial, operational, and economic viability of a clothing brand for children up to 5 years old, which focuses mainly on offering the option of personalizing the garments and outfits of the child just like their mother wishes. Mothers could be able to build the designs with or help or adapt the existing designs with the customizations that the mother wishes. The target market is made up for mothers between 25 and 44 years old who have children up to 5 years old and who live in zones 6, 7 and 8 of Lima. It is estimated that the projected demand by 2026 (fifth year) will be 2,713 orders, whose average ticket value will be S/296.00 including VAT and will be served through virtual sales channels. The brand's textile workshop is in La Molina, with an area of 70 m², the layout and services necessary for the operation and with a very advantageous location, since it is located near to the principal suppliers and is a central district for the distribution to the objective’s clients. In order to the brand to start operations, the shareholders invested S/ 15,000.00 soles. This amount was not a big number because the shareholders had already a company established, and some installation and procedures expenses not had to be disbursed. In addition, since the brand has one year of operation (2021), to carry out the economic evaluation, the real accounting data of the brand in its first year were considered to find the values of VAN and TIR and it was obtained a value of S/. 85,582.00 soles for VAN and 131% for TIR. This result indicates that the current project is viable and profitable so that its operation continues and grows as it has been happening.